The effect of glycemic index on plasma glucose and lactate levels during incremental exercise - Stannard, S. R.; Thompson, M. W.; Brand Miller, J. C. (International Journal of Sport Nutrition and Exercise Metabolism, 2000)
Consumption of low glycemic index (GI) foods before submaximal endurance exercise may be beneficial to performance. To test whether this may also be true for high intensity exercise, 10 trained cyclists began an incremental exercise test to exhaustion 65 min after consuming equal carbohydrate portions of glucose (HGI), pasta (LGI), and a noncarbohydrate control (PL). Time to fatigue did not differ significantly (p = 0.05) between treatments. Plasma glucose concentration was significantly lower after LGI vs. HGI from 15 to 45 min of rest postprandial. During exercise, plasma glucose concentration was significantly lower after HGI vs. LGI from 200 W until exhaustion. Plasma lactate of rest postprandial through to the end of the 200-W workload. Plasma lactate concentration following LGI was significantly lower than after HGI from 45 min of rest postprandial through to the end of the 100-W workload. At higher exercise intensities, there was no significant difference in plasma lactate levels between treatments. These findings suggest that a high GI carbohydrate meal (1 g/kg body wt) 65 min prior to exercise decreases plasma glucose and increases plasma lactate levels compared to a low GI meal, but not enough to be detrimental to incremental exercise performance.